2008
DOI: 10.1007/s00586-008-0602-4
|View full text |Cite
|
Sign up to set email alerts
|

European guidelines for the diagnosis and treatment of pelvic girdle pain

Abstract: A guideline on pelvic girdle pain (PGP) was developed by "Working Group 4" within the framework of the COST ACTION B13 "Low back pain: guidelines for its management", issued by the European Commission, Research Directorate-General, Department of Policy, Coordination and Strategy. To ensure an evidence-based approach, three subgroups were formed to explore: (a) basic information, (b) diagnostics and epidemiology, and (c) therapeutical interventions. The progress of the subgroups was discussed at each meeting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
577
1
17

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 682 publications
(643 citation statements)
references
References 119 publications
10
577
1
17
Order By: Relevance
“…Our randomized trial differed in design and intervention compared to a US randomized trial; in the US study, nonsurgical management included intraarticular SIJ steroid injections and radiofrequency (RF) ablation. Instead, our trial included only PT and adequate information and reassurance, consistent with European guidelines for pelvic girdle pain [29]. We note that although SIJ steroid injections and RF ablation are not commonly delivered in Europe, many trial participants had already undergone such treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our randomized trial differed in design and intervention compared to a US randomized trial; in the US study, nonsurgical management included intraarticular SIJ steroid injections and radiofrequency (RF) ablation. Instead, our trial included only PT and adequate information and reassurance, consistent with European guidelines for pelvic girdle pain [29]. We note that although SIJ steroid injections and RF ablation are not commonly delivered in Europe, many trial participants had already undergone such treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management was designed according to the European guidelines for the diagnosis and management of pelvic girdle pain [29]. CM consisted of (1) optimization of medical therapy, (2) individualized physical therapy (PT) that focused on mobilization and stabilization exercises for control and stability, and (3) adequate information and reassurance of the patient as part of a multifactorial treatment.…”
Section: Interventionsmentioning
confidence: 99%
“…There were several reasons given for not seeking treatment: mild intensity or low frequency of pain, absence of health professional referral, believing that LBP is normal during pregnancy, use of other relief strategies and lack of awareness of possible treatments. However, physiotherapy is an effective treatment for LBP during pregnancy [13], and referral should be considered to prevent or reduce LBP and enhance the quality of life of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Massage therapy has been shown to be effective for reducing LBP and decreasing levels of anxiety [10]. Carr [11] indicated that the use of orthotheses such as sacroiliac belts can significantly reduce pain and lessen the effects on daily life; however, Vleeming et al [13] identified no evidence for the use of a pelvic belt as a stand-alone treatment. Transcutaneous electrical nerve stimulation can also be used, but tends to be the last treatment option, when other treatments are not effective [12].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Current terminology, pain topography, functional disabilities, and positive correlation of clinical testing have demarcated the classification of pregnancy-related lumbopelvic pain (PR LPP) into subgroups: pregnancy-related low back pain (PR LBP) and pregnancy-related pelvic girdle pain (PR PGP). [2][3][4] Careful observation of the clinical features of PR LPP can help distinguish the seriousness of the potential symptoms and prognosis. Pain has shown to influence pregnant women's daily lives and the challenges they encounter concerning their physical, psychological, occupational, and social function.…”
Section: Introductionmentioning
confidence: 99%